2021
DOI: 10.1007/s12144-021-02105-8
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of health literacy on the relationship between health care system distrust and vaccine hesitancy during COVID-19 pandemic

Abstract: This study explores the mediating role of health literacy on the association between health care system distrust and vaccine hesitancy. An online survey including Personal Information Form, Health Care System Distrust Scale, Vaccine Hesitancy Scale, and Health Literacy Scale were applied to 620 participants. The degree of applying mask-wearing, hygiene rule and physical distance, and the level of COVID-19 vaccine literacy were modeled with hierarchical multiple regression analysis to have a deeper analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 54 publications
4
65
0
5
Order By: Relevance
“…On the contrary, data from Ireland, Italy and Spain showed that education above primary level was associated with lower chances of flu vaccination uptake [38]. The inverted trend toward vaccine uptake in Italy according to education level observed in our study could be explained, on the one hand, by the evolving and dynamic nature of vaccine hesitancy [39] and, on the other, by the potential advantage of more highly educated respondents when it comes to interpreting information regarding vaccines within the context of a pandemic [35,40]. Although digital health literacy and different information seeking behaviours [41] have not been explored in our questionnaire, it could be speculated that changes in digital health literacy during the last decade might have resulted in-in highly educated individuals-better knowledge about influenza vaccination and therefore led to a higher uptake.…”
Section: Discussionsupporting
confidence: 40%
“…On the contrary, data from Ireland, Italy and Spain showed that education above primary level was associated with lower chances of flu vaccination uptake [38]. The inverted trend toward vaccine uptake in Italy according to education level observed in our study could be explained, on the one hand, by the evolving and dynamic nature of vaccine hesitancy [39] and, on the other, by the potential advantage of more highly educated respondents when it comes to interpreting information regarding vaccines within the context of a pandemic [35,40]. Although digital health literacy and different information seeking behaviours [41] have not been explored in our questionnaire, it could be speculated that changes in digital health literacy during the last decade might have resulted in-in highly educated individuals-better knowledge about influenza vaccination and therefore led to a higher uptake.…”
Section: Discussionsupporting
confidence: 40%
“…Healthcare system distrust as well as vaccine hesitancy are suggested to be closely related to health literacy [67]. Heidari et al [68] emphasized the need for an intersectional gender approach to vaccine development and deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of translated culturally tailored health information from reputable sources combined with misinformation exposure through social networks and social media may further erode trust in health systems, employers, or public institutions. Mistrust can then lead to poor compliance with public health and occupational health guidance such as proper workplace personal protective equipment (PPE) use and further increasing infection risk (50,51).…”
Section: Disproportionately High Covid-19 Infection Hospitalization A...mentioning
confidence: 99%